Analysis on Anies Baswedan's leadership as Jakarta's governor through Instagram on 2021-2022 - Ravyanda Awallun; Ahmad Chumaedy; Yusuf Fadli; Toddy Aditya; Riska Sarofah (Jurnal Studi Komunikasi, 2024)
This study aims to analyse Anies Baswedan's political leadership during his tenure as Governor of Jakarta Province through Instagram in 2021-2022. The focus of this research is the Theory of Political Leadership proposed by Andrew Heywood (2015): leadership as (1) Behaviour patterns, (2) Personal qualities, and (3) Political values. This article uses qualitative research methods and descriptive analysis approaches conducted using NVivo 12 Plus software. The results of this study revealed that Anies Baswedan's political leadership through Instagram is highly focused on showing performance that describes personal qualities in carrying out duties as Governor of Jakarta Province. Anies Baswedan's political leadership has also been characterised by numerous initiatives in the social and infrastructure sector that Anies Baswedan has fulfilled over the past year (2021-2022). Anies Baswedan was also very active in using social media platforms such as Instagram during his time as Governor to convey some of his political leadership activities such as informing work programs, political branding, political communication, success in leading the capital, togetherness with family, citizens, and political leaders of Indonesia and even the world.